Exploration on Chinese Traditional Culture in Chinese Film and TV Works - sixian, Sun; Tungkavet, Wanwirat (International Journal of Development Administration Research, 2021)
With the further development of social economy, modern film and television works have transformed into a common form of People’s Daily entertainment as people are increasingly speeding up their pace of life and enhancing their demand of stimulation, but the works has lost their cultural communication function. In order to better convey Chinese traditional culture, modern Chinese film and television works should show traditional Chinese cultural elements which should be concentrated on by the film and television industry to explore the pathways to put Chinese traditional cultural elements in Chinese film and television works.